IbM Underwear Rules Dalam Upaya Pencegahan Kekerasan Seksual pada Anak Usia Dini - Ernawati, Dwi; Ningsih, Sri Ratna (Jurnal Pengabdian Dharma Bakti, 2019)
Prevention of sexual violence in children can be done by some particular method. The method used in this community service is under wear rule. The underwear rules are simple guidelines to help parents or teachers explain to children that other people should not try to touch them, how they should react and where can they seek help. From the data summarized from Harian Terbit, based on National Commission of Children Protection recorded from January to April 2014, there were 342 cases of sexual violence against children. Data from the National Police in 2014 recorded that there were 697 cases of sexual violence against children that occurred in half of 2014. Of that number, 726 people were arrested with the number of victims reaching 859 people. Whereas National Commission of Children Protection data from January to April 2014 showed that there were 622 reports of violent cases against children (Setyawan 2014). The resulting outputs are 1) The arrangement of the booklet 2) The formation of promotional media in the form of power points, 3) The evaluation form of children's understanding of underwear rule, 4) The movie maker of service activities, 5) Publication. The result obtained that children could understand about the underwear rule. Based on this community service program, schools and families are expected toÂ participate in teaching children about underwear rules to prevent sexual violence in childrenKeywords: violence, childrenâ€™s,prevent